Gilotyna . niezależne pismo młodzieży szkolnej, no. 4, 1981 - I LO, [ed. Janusz P. Waluszko et al.] ([s.n., 1981)
Motto: "Fight! Overcome oneself! Surmount disease, madness, death… But how to fight, how to win?" Wiera Figner